Investigation of the electron kinetics in O2 capacitively coupled plasma with the use of a Langmuir probe. (9th May 2017) - Kechkar, S; Swift, P; Kelly, S; Kumar, S; Daniels, S; Turner, M
Abstract: A Langmuir probe was used to measure various electron plasma parameters in O2 capacitively coupled plasma. It was shown that the variation in these plasma parameters was due to changes in the electron heating mechanisms as the discharge conditions varied. The so called ' α – γ ' mode transition in O2 plasma (100 mTorr) was identified from the power evolution (30–600 W) of the electron energy probability function (EEPF), electron density ( n e ) and effective electron temperature ( T eff ). The EEPF evolved from Druyvesteyn to bi-Maxwellian with increasing applied power which resulted in a rapid decrease and an abrupt increase in T eff and n e respectively. Comparisons were made to the same mode transition for similar conditions in Ar plasma. The EEPFs were Druyvesteyn in the α mode and evolved into a Maxwellian like EEPF in the γ mode of an Ar plasma. Two distinct trends of n e versus power was observed, it was shown that the measured rf current and rf voltage had a similar behavior. The pressure evolution of the EEPF, n e, and T eff was also investigated in O2 plasma operated at both 30 and 200 W. At 30 W the number of high energy electrons decreased and flattening of the low energy portion of the EEPF occurred with increasing gas pressure (10–100 mTorr) which indicates a collisionless to collisional heating transition. However, at 200 W the right combination of rf voltage and pressure was met for the discharge to evolve into the γ mode as the pressure increased. This was evident from significant narrowing of the EEPF as the pressure increased.